2005
DOI: 10.1021/ie0489352
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mixture Diffusion in Nanoporous Adsorbents via the Pressure-Swing Frequency Response Method. 2. Oxygen and Nitrogen in a Carbon Molecular Sieve

Abstract: A simple apparatus using the pressure-swing frequency response method has been extended to measure multicomponent diffusivities. Transfer phenomena are investigated for different compositions of a binary mixture of nitrogen and oxygen in a carbon molecular sieve. The paper has two objectives. First, we consider the applicability of some predictive multicomponent diffusion models, which predict the mixture diffusivities based on pure-component information.The results show that these models can provide qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Similar trends were observed for the N 2 -O 2 mixture on 4A at 273 K [92]. Later, Wang and LeVan [94] applied the flow-through PSFR system to investigate the N 2 -O 2 mixture in CMS system at several concentrations and found the cross-term diffusivities can be essential to describe mass transfer rates for mixture separation of kinetic origin. Their correlation results showed that the main-term diffusivities are weak functions of the concentration, while the diffusive cross-terms are strong functions of the composition.…”
Section: Multi-component Mixtures In Microporous Materialssupporting
confidence: 62%
“…Similar trends were observed for the N 2 -O 2 mixture on 4A at 273 K [92]. Later, Wang and LeVan [94] applied the flow-through PSFR system to investigate the N 2 -O 2 mixture in CMS system at several concentrations and found the cross-term diffusivities can be essential to describe mass transfer rates for mixture separation of kinetic origin. Their correlation results showed that the main-term diffusivities are weak functions of the concentration, while the diffusive cross-terms are strong functions of the composition.…”
Section: Multi-component Mixtures In Microporous Materialssupporting
confidence: 62%
“…In general, the kinetics or mass transfer rate of adsorption and desorption of a pure gas in a microporous adsorbent can be controlled by a single mechanism, like micropore diffusion, macropore diffusion, or macropore advection, or any combination of these mechanisms . In recent decades, frequency response (FR) methods have proven to be one of the best macroscopic techniques for investigating the kinetic behavior of gas adsorbate–adsorbent systems due to their ability to discriminate among different rate limiting mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Besides VFR, another type of widely used frequency response is a flow-through technique that involves perturbation of variables like inlet flow rate, inlet stream concentration, or pressure. In recent years, LeVan and co-workers used a combined frequency response technique using volumetric and flow-through experiments to study pure gas mass transfer rates in adsorbents or combined pressure-swing and concentration-swing frequency response experiments to study mass transfer rates for both single and mixed gases in various adsorbents. , Most recently, Wang et al used a pressure swing frequency response to study the mass transfer mechanism of ethane in ZIF-8 material and verified the results against VFR.…”
Section: Introductionmentioning
confidence: 99%
“…47 The model developed for the concentration swing apparatus is similar to the model used to describe the dynamics of their pressure swing frequency response apparatus. [48][49][50] It should be noted that most of the FR works discussed above assume that small perturbations to the system allow for portions of the kinetic model to be linearized. However, several studies have investigated nonlinear kinetic modeling of FR data.…”
Section: Introductionmentioning
confidence: 99%